Electrooxidation Behavior and Amperometric Determination of Sotalol on a Graphene Oxide Nanosheets-modified Glassy Carbon Electrode - Heli, Hossein; Zare, Seyede Nasrin; Sattarahmady, Naghmeh; Karimian, Khashayar (Current Pharmaceutical Analysis, 2013)
The electrochemical behavior of sotalol was investigated on a graphene oxide nanosheets-modified glassy carbon electrode in a phosphate buffer solution, pH 7.4. Cyclic voltammetry and chronoamperometry were employed to obtain information about the electrooxidation process. During the electrooxidation of sotalol, one irreversible anodic peak appeared in the voltammograms. Some kinetic parameters, such as the diffusion and charge transfer coefficients were obtained. An amperometric procedure was developed for the determination of sotalol, a detection limit of 7.57 μM, a linear dynamic range of 0.1 to 2.24 mM, and a calibration sensitivity of 0.945 mA M-1 were obtained. The method was applied to the analysis of sotalol tablets, and applicability of the method to direct assays of spiked human serum and urine fluids was investigated.
Keywords: sotalol